Gastrointestinal Parasites of Farmed White-tailed Deer (Odocoileus virginianus) in Florida - Sydney L. Cottingham; Heather D.S. Walden; Samantha M. Wisely; Juan M. Campos-Krauer (EDIS)
White-tailed deer are susceptible to infection by numerous gastrointestinal parasites. Not all parasite infections cause clinical disease, but even subclinical gastrointestinal parasitism may reduce the health and productivity of infected deer.  An understanding of parasite epidemiology is critical to improving captive deer health through effective parasite control strategies. This publication will serve as a guide to common parasites of farmed white-tailed deer in Florida and will provide producers with recommendations for management of gastrointestinal parasites in farmed deer.